Validation of the Clinical Global Impression—Corrections Scale (CGI-C) by Equipercentile Linking to the BPRS-E - Jones, Roland M.; Gerritsen, Cory; Maheandiran, Margaret; Simpson, Alexander I. F. (Frontiers in Psychiatry, 2020)
Background The Clinical Global Impression – Corrections (CGI-C) is an adaptation of the severity scale of the Clinical Global Impression for use in correctional facilities. Although it has been shown to have good inter-rater reliability, there have been no validation studies of this instrument. Method We analysed data from 726 initial assessments of persons detained in two correctional facilities and compared clinicians ratings for the CGI-C and Brief Psychiatric Rating Scale-Expanded (BPRS-E). We used equipercentile linkage and Spearman correlations to investigate concordance in the total sample, by diagnostic groups, and by gender. Results We found that the CGI-C scores and BPRS-E scores among persons in remand settings were significantly correlated (ρ =0.51, p<0.001) and that correlations were the same for men and women. We found that points of equivalence can be reliably found between the two scales using equipercentile linkage, and that those with psychotic disorders had lower BPRS-E scores than those with mood/anxiety/situational stress for equivalent CGI-C scores. Conclusion Overall, CGI-C ratings correspond well to BPRS-E ratings for both men and women remand prisoners across diagnoses, and the CGI-C appears to be a valid tool for the assessment of severity of symptoms in this setting.